2007
DOI: 10.1128/jb.00105-07
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Gene Transfer and Homologous Recombination Drive the Evolution of the Nitrogen-Fixing Symbionts of Medicago Species

Abstract: Using nitrogen-fixing Sinorhizobium species that interact with Medicago plants as a model system, we aimed at clarifying how sex has shaped the diversity of bacteria associated with the genus Medicago on the interspecific and intraspecific scales. To gain insights into the diversification of these symbionts, we inferred a topology that includes the different specificity groups which interact with Medicago species, based on sequences of the nodulation gene cluster. Furthermore, 126 bacterial isolates were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0
12

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 58 publications
(61 reference statements)
5
62
0
12
Order By: Relevance
“…In the case of rhizobia, Minamisawa et al (22) suggested the potential horizontal transfer of nod genes among bradyrhizobia and other bacterial populations in soil environments. Similarly, Bailly et al (2) suggested that during the evolution of Medicago symbionts, horizontal transfer of nod genes might have occurred either to the common ancestor of the two Ensifer species or to one Ensifer species followed by the other. Additionally, Suominen et al (34), when describing the structure of the common nodulation genes of Rhizobium galegae, reported that lateral nod gene transfer might have occurred from fast growing rhizobia to agrobacteria.…”
mentioning
confidence: 99%
“…In the case of rhizobia, Minamisawa et al (22) suggested the potential horizontal transfer of nod genes among bradyrhizobia and other bacterial populations in soil environments. Similarly, Bailly et al (2) suggested that during the evolution of Medicago symbionts, horizontal transfer of nod genes might have occurred either to the common ancestor of the two Ensifer species or to one Ensifer species followed by the other. Additionally, Suominen et al (34), when describing the structure of the common nodulation genes of Rhizobium galegae, reported that lateral nod gene transfer might have occurred from fast growing rhizobia to agrobacteria.…”
mentioning
confidence: 99%
“…Rhizobial genetic plasticity underlies the adaptation of numerous bacterial species to thriving with legumes -a group of plants susceptible to bacterial molecular signals [13], but the detailed role of the different processes participating in this plasticity during evolution of symbioses is still controversial. Some authors emphasize the role of lateral genetic transfer in rhizobial evolution [39,40,[100][101][102][103], whereas others suggest the lateral transfer of nodulation genes occurred in minority of cases [104,105]. Moreover, frequent genetic transfer and recombination events were evidenced within species (between sublineages) in different models [11,36,42,43,49,101].…”
Section: Changes In Rhizobial Populations Resulting From Plant-bactermentioning
confidence: 99%
“…Moreover, some of them are selftransmissible or can be transferred to other bacterial cells in the presence of other plasmids [35,36]. The frequency of plasmid transfer between rhizobial strains and the role of this genetic exchange in rhizobial evolution remains controversial [37][38][39][40]. However, the pool of plasmid replicons present in rhizobial cells is regarded as a (mostly) accessory genetic component which is evolving more rapidly than the chromosome [33], due to frequent changes (such as gene duplication, mutation or deletion) within particular replicons [41] or rearrangements between different replicons [42,43].…”
Section: Rhizobial Genomes -A Scheme For Extraordinary Strain Diversitymentioning
confidence: 99%
“…Plasmid evolution is further affected by frequent movement of extrachromosomal replicons among the strains. In fact, some of these elements may be transferred to other bacterial cells by itself or in the presence of other mobilizing plasmids [73,92,110,111]. Cervantes et al [123] showed that Sfr plasmids might originate through the transfer of a symbiotic-conjugative-plasmid from the Rhe to a Sfr strain and at least two further recombination events among the Rhe plasmids and the Sfr genome.…”
Section: The Impact Of Postgenomic Knowledge To Rhizobial Plasmid Rolmentioning
confidence: 99%
“…The comparative analyses of genomic features and a single-nucleotide polymorphism pattern on different replicons of Sinorhizobium spp. genomes clearly demonstrated that DNA recombination among closely related bacteria was a major event in the diversification of these genomes, especially in pSymA, resulting in its mosaic structure [71][72][73].…”
Section: Rhizobial Plasmids Structure Gene Content and Impact On Bacmentioning
confidence: 99%